Serum biomarkers in the metabolic dysfunction-associated steatotic liver fibrosis diagnosis in children - Yu.M. Stepanov; N.Yu. Zavhorodnia; I.A. Klenina; O.M. Tatarchuk; O.P. Petishko (Gastroenterologìa)
Background. The COVID-19 epidemic and the war in Ukraine have led to a significant increase in the number of children suffering from metabolic dysfunction-associated steatotic liver disease (MASLD). One of the unresolved problems associated with MASLD is the identification of individuals at risk of rapid disease progression and development of irreversible liver changes. The search for alternative noninvasive markers suitable for the early detection of liver fibrosis in children remains extremely relevant. The aim of the study was to determine the diagnostic value of serum fibrosis markers and their relationship with sonographic and body composition parameters in children with MASLD. Materials and methods. The case-control study included 80 children aged 6 to 17 years (mean of (12.15 ± 2.51) years). The presence of steatosis and liver fibrosis was determined by transient elastography (FibroScan® 502 touch F60156, Echosens, France). All subjects underwent anthropometric studies to determine body mass index. If it was within one-two Z-score, overweight was diagnosed. If the body mass index exceeded two Z-score, obesity was diagnosed. According to transient elastography and body mass index, all children were divided into four groups: group I — 27 children with MASLD and fibrosis ≥ F1, group II — 35 children with MASLD without fibrosis, group III — 18 obese or overweight children without MASLD and without fibrosis. The control group IV consisted of 14 children with normal weight without MASLD and without fibrosis. The groups had no significant differences in age and gender distribution. The study of body composition was performed by bioimpedance analysis using a TANITA MC-780MA analyzer (manufactured by Maeno-cho, Itabashi-ku, Tokyo, Japan). Quantitative determination of the serum concentration of vascular endothelial growth factor (VEGF) was performed by enzyme-linked immunosorbent assay (ELISA) using test systems from Wuhan Fine Biotech Co., Ltd (China) according to the manufacturer’s recommendations. The level of serum cytokeratin 18 (CK-18) was evaluated with IDL Biotech AB kits (Sweden) for ELISA. Serum content of transforming growth factor beta 1 (TGF-β1) was studied using an ELISA test system from IBL International (Germany). Fibrogenesis processes were evaluated by the serum content of free hydroxyproline (HPf), protein-bound hydroxyproline (HPp/b) and glycosaminoglycans (GAG). Results. The study revealed a significant increase in the level of CK-18 and TGF-β1 in children with MASLD-associated liver fibrosis. In children with liver fibrosis, an increase in the ratio of HPf/HPp/b and the level of GAG in the blood serum was observed compared to patients with MASLD without fibrosis and with overweight and obese children. The threshold value of CK-18 for liver fibrosis diagnosis was 90.3 U/l (sensitivity 81.3 %, specificity 76.9 %, AUC 0.843, p < 0.001). The sensitivity of the threshold value of serum TGF-β1 (96.8 pg/mL) in children with MASLD was 80.0 %, specificity 65.7 %, AUC 0.787 (p < 0.001). Threshold value of serum GAG (4.24 mmol/L) demonstrated a sensitivity of 70.6 % and a specificity of 69.6 %, AUC 0.743 (p < 0.01). CK-18, TGF-β1, GAG shown a positive correlation with liver stiffness and elasticity, body composition of MASLD children and had high levels of diagnostic accuracy, which allows them to be used in children when screening for MASLD-associated liver fibrosis. Conclusions. Children with liver fibrosis are characterized by elevated serum levels of CK-18, VEGF, TGF-β1, HPp/b and GAG. The threshold values of CK-18 (more than 90.3 U/l), TGF-β1 (above 96.8 pg/mL) and GAG (more than 4.24 mmol/l) have high sensitivity and specificity, which allows them to be used for the diagnosis of liver fibrosis in children with MASLD.